Electron Microscopic, Genetic and Protein Expression Analyses of Helicobacter acinonychis Strains from a Bengal Tiger - Tegtmeyer, Nicole; Traverso, Francisco Rivas; Rohde, Manfred; Oyarzabal, Omar A.; Lehn, Norbert; Schneider-Brachert, Wulf; Ferrero, Richard L.; Fox, James G.; Berg, Douglas E.; Backert, Steffen (PLoS ONE, 2013)
Colonization by Helicobacter species is commonly noted in many mammals. These infections often remain unrecognized, but can cause severe health complications or more subtle host immune perturbations. The aim of this study was to isolate and characterize putative novel Helicobacter spp. from Bengal tigers in Thailand. Morphological investigation (Gram-staining and electron microscopy) and genetic studies (16SrRNA, 23SrRNA, flagellin, urease and prophage gene analyses, RAPD DNA fingerprinting and restriction fragment polymorphisms) as well as Western blotting were used to characterize the isolated Helicobacters. Electron microscopy revealed spiral-shaped bacteria, which varied in length (2.5-6 μm) and contained up to four monopolar sheathed flagella. The 16SrRNA, 23SrRNA, sequencing and protein expression analyses identified novel H. acinonychis isolates closely related to H. pylori. These Asian isolates are genetically very similar to H. acinonychis strains of other big cats (cheetahs, lions, lion-tiger hybrid and other tigers) from North America and Europe, which is remarkable in the context of the great genetic diversity among worldwide H. pylori strains. We also found by immunoblotting that the Bengal tiger isolates express UreaseA/B, flagellin, BabA adhesin, neutrophil-activating protein NapA, HtrA protease, γ-glutamyl-transpeptidase GGT, Slt lytic transglycosylase and two DNA transfer relaxase orthologs that were known from H. pylori, but not the cag pathogenicity island, nor CagA, VacA, SabA, DupA or OipA proteins. These results give fresh insights into H. acinonychis genetics and the expression of potential pathogenicity-associated factors and their possible pathophysiological relevance in related gastric infections. © 2013 Tegtmeyer et al.
Created from Fastlane, Scopus look-up